ANALISIS KEPRIBADIAN TOKOH DATUK IDA GURNADI DALAM CERITA RAKYAT DESA SINGOROJO KABUPATEN JEPARA - Hidayatullah, Romadhoni Shiddiqi; Hidayah, Siti Nur; Kanzunnudin, Mohammad (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the personality of Datuk Ida Gurnadi as portrayed in the folklore of Singorojo Village, Jepara Regency, and its relevance to character education. The folklore analyzed is derived from the book Cerita Rakyat Pesisir Timur written by Mohammad Kanzannudin (2023), which presents the life journey of Ida Gurnadi as an important figure in the formation of Singorojo Village. This research employs a descriptive qualitative method with a literary studies approach. The data consist of narrative elements, events, and characters’ actions that reflect the personality of Datuk Ida Gurnadi, which are analyzed through data reduction, classification, and interpretation. The findings reveal that Datuk Ida Gurnadi exhibits religiousness, responsibility, and courage as core personality traits, reflected in his attitudes and social roles within the community. These values are relevant to character education and can be integrated into Indonesian language and literature learning, particularly through the use of folklore as contextual teaching material. The implications of this study indicate that folklore can serve as an effective learning medium for instilling character values while enhancing students’ literary appreciation and understanding of local culture.